CORROSION PROTECTION ABILITY OF POLYPYRROLE COATED MILD STEEL IN BURIED SAND - Singh, Sanjay; Neupane, Shova; Karki, Nabin; Gupta, Dipak Kumar; Yadav, Amar Prasad (Bangladesh Journal of Multidisciplinary Scientific Research, 2025)
Corrosion prevention is a global issue. One way to reduce metal corrosion is by applying polymer coatings. Corrosion prevention increasingly involves the use of polypyrrole (PPy) coatings, which significantly reduce corrosion rates and provide anodic protection. The purpose of this study was to deposit PPy on mild steel (MS) from 0.4 M pyrrole in 0.1 M sodium potassium (Na-K tartrate) by cyclic voltammetry (CV). This study employed electrodeposition of PPy on MS by CV and explored its corrosion protection performance in the buried sand medium containing 0.1 M NaCl and 0.1 M H2SO4 by the potentiodynamic polarization (PDP) method. The results revealed that with an increase in the number of cycles, the CV showed that the PPy layer formed gradually and covered the MS surface. The oxidation peak vanished after the first cycle, and the current increased with the increasing cycles. The synthesized PPy coating was analyzed by a scanning electron microscope (SEM), which revealed a compact coating layer with cauliflower-like morphology. It was also examined using an energy-dispersive X-ray spectrometer (EDX), which confirmed the presence of carbon, nitrogen, and oxygen elements. The open-circuit potential (OCP) remained constant over time, resulting in a stable film. The corrosion potential also showed a slight change compared to both media. The significant findings of this study were that the PPy coating behaved as a mixed inhibitor in both media, and the corrosion inhibition efficacy of the PPy coating was approximately 99% in H2SO4 and 98% in NaCl, with good adhesion. JEL Classification Codes: L6, L69.